The Passion: Jeanette Winterson’s Uncanny Mirror of Ink - Susana Onega (Miscelánea: A Journal of English and American Studies, 1993)
In keeping with the contradictory nature of the postmodernist ethos, The Passion combines three apparently opposed elements: a realism-enhancing interest in history and story-telling, a heavily parodic and ironic relish in self-referentiality, and the zest for the uncanny epistemological uncertainty characteristic of fantasy literature. The combination of these three elements, the historical, the metafictional and the fantastic, produces an overall effect of fragmentation which is, however counterbalanced by the possibility of a unitarian reading of the novel that goes through the perception of its unifying myth: the journey or quest, already hinted at in the novel’s epigraph and developed in the text at three major levels: the archetypal, the psychological and that of Tarot symbolism.